Ontology, Epistemology, and Axiology in Guidance and Counseling Science Through the Integration of Stoicism - Halimahtun Syaddiyah; Yeni Karneli; Puji Gusri Handayani (Journal Of Psychology, Counseling And Education, 2025)
The urgency of strengthening the philosophical foundation in Guidance and Counseling (BK) is increasing along with the complexity of adolescent psychosocial problems in the modern era. This article aims to critically analyze the ontological and epistemological dimensions in the science of guidance and counseling and its contribution to reflective counseling practices. This research uses a qualitative descriptive approach through a literature study of relevant academic sources. The results of the study show that ontological understanding of human nature and epistemology related to sources of knowledge in counseling can enrich contextual and meaningful counseling practices. The integration of Stoicism philosophy - with values such as self-control and acceptance of reality - was found to be effective in helping adolescents manage stress. This study contributes to the development of a more philosophical, spiritual and locally value-adaptive conceptual framework for counseling. The study recommends empirical exploration to test the effectiveness of this approach across different cultural contexts.